Education as a necessity of life: - Muweesi, Charles; Namukose, Sarah; Muwagga, Mugagga Anthony (British Educational Research Association, 2024)
Every country desires and aspires for an education system that caters for learners’ physiological needs, belonging, love, self-esteem, security and self actualisation at the top, which are rarely provided by a few countries. With a review focus on the Ugandan education system, several challenges related to the education borrowing suggestions as proposed by John Dewey have been attributed to creating an environment that has seen most graduates ending up unemployed, and with leadership challenges, inadequate funding, poor teacher perception, low research and innovations in higher institutions of learning, less involvement of the informal sector in development, low literacy levels, political interference among others. Thus this exploratory analytical-qualitative review focuses on John Dewey's teachings in his book Education and Democracy—specifically chapter 1, ‘Education as Necessity for Life’—with attention on how education as an engine that empowers life, ensures independence through self-reliance, sustenance, freedom, and is syndrome-free to enhance appreciation of the contemporary trends in education—critical aspects that are extremely lacking within the current Ugandan education system and can impact on the future of education to the future of education as recommended in National Development Plan III (NDP III). Thus the review recommends that while reflecting on the state of the Ugandan education system, there is a need to revitalise the research and innovations in higher institutions, especially catering for an integral-education system with a focus on science, technology, engineering and mathematics (STEM) from primary school to university, involvement of the informal sector through skills education as proposed by the Ugandan Vision 2040 and NDP III, as well as addressing low literacy levels and providing adequate Teaching and learning through quality and balanced funding from all relevant government agencies and development partners. KEYWORDS Education philosophy, international and comparative education, education policy
an exploration on Ugandan Education System Quality with reference to John Dewey's Philosophical Correlates.
Article